RNA Related to That of a Murine Leukemia Virus in Burkitt's Tumors and Nasopharyngeal Carcinomas - Kufe, D. (1973)
RNA homologous to that of the Rauscher leukemia virus has been detected in Burkitt's lymphomas and nasopharyngeal carcinomas. Earlier excellent experimental evidence has linked these two human tumors with the Epstein-Barr virus, a DNA-containing agent.